Biosynthesis of zinc oxide nanoparticles using culture filtrates of Aspergillus niger: Antimicrobial textiles and dye degradation studies - V.N. Kalpana; Bala Anoop Sirish Kataru; N. Sravani; T. Vigneshwari; A. Panneerselvam; V. Devi Rajeswari (Elsevier, 2018)
The main goal of undertaking the current investigation was to evaluate the extracellular synthesis of ZnO NPs using culture filtrates of Aspergillus niger. The obtained UV-Visible spectrum of the culture filtrate showed an absorption peak at 320 nm. The FTIR band showed the appearance of carboxylic acid and strong aromatic ring that could be responsible for the synthesis of ZnO NPs. Studies of the antimicrobial activity of ZnO NPs coated fabric showed a reduction of viable E. coli and S. aureus. 90% of decolorization of Bismarck brown dye was obtained by treating it with 100 µl ZnO NPs. The Germination (%) of the seeds of plants was lower with the raw dye when compared to the dye treated with ZnO NPs. The present study concludes that the A. niger mediated synthesis of ZnO NPs proved well in degrading dye and can be incorporated onto cotton fabrics since it reveals antibacterial activity. Keywords: A. niger, Zinc oxide nanoparticles, Bismarck brown, Pisum sativum